BACH1, the master regulator of oxidative stress, has a dual effect on CFTR expression. Issue 20 (29th October 2021) - NandyMazumdar, Monali; Paranjapye, Alekh; Browne, James; Yin, Shiyi; Leir, Shih-Hsing; Harris, Ann
Abstract : The cystic fibrosis transmembrane conductance regulator ( CFTR ) gene lies within a topologically associated domain (TAD) in which multiple cis -regulatory elements (CREs) and transcription factors (TFs) regulate its cell-specific expression. The CREs are recruited to the gene promoter by a looping mechanism that depends upon both architectural proteins and specific TFs. An siRNA screen to identify TFs coordinating CFTR expression in airway epithelial cells suggested an activating role for BTB domain and CNC homolog 1 (BACH1). BACH1 is a ubiquitous master regulator of the cellular response to oxidative stress. Here, we show that BACH1 may have a dual effect on CFTR expression by direct occupancy of CREs at physiological oxygen (∼8%), while indirectly modulating expression under conditions of oxidative stress. Hence BACH1, can activate or repress the same gene, to fine tune expression in response to environmental cues such as cell stress. Furthermore, our 4C-seq data suggest that BACH1 can also directly regulate CFTR gene expression by modulating locus architecture through occupancy at known enhancers and structural elements, and depletion of BACH1 alters the higher order chromatin structure.